Gestalt Counseling with Empty Chair Technique to Reduce Guilt among Adolescents at Risk - Trijayanti, Yessinta Wahyu; Nurihsan, Juntika; Hafina, Anne (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2019)
Adolescent is defined as a period of transitional development from childhood to adulthood. This transition also requires adolescents to make some adjustment. Those who cannot adjust themselves to the transition may induce guilt in them. Guilt is an emotion that follows after a negative behavior. Gestalt counseling with empty chair technique can help counselees finish their